Research on Indigenous Knowledge and its Application: A Case of Wild Food Plants of Zimbabwe - Soul Shava (Environmental Association of Southern Africa, 2005)
Research on indigenous knowledge should go beyond documenting and interpreting it. Rather, it should stimulate inquiry into its application in present day community development and education settings. This study intends to steer indigenous knowledge research towards practical application initiatives. The study documents wild food plants of Zimbabwe, highlights some popular wild food plants, and cites some commercially marketed wild food plants and makes recommendations on the application of indigenous knowledge of wild food plants in community and educational settings.